Sustainability reporting and board diversity in Malaysia - Sheikh Abu Bakar, Aishah; Mohd Ghazali, Nazli Anum; Ahmad, Maslina (Zes Rokman Resources (2131022-P), 2019)
Board diversity is believed to enhance companies’ strategies and decision-making process which lead to companies’ sustainability in business. This study focuses on the gender, age and ethnic diversity and the objective is to examine the impact of these board diversity elements on the extent and quality of sustainability reporting (SR) among the top 100 Malaysian listed companies. Data is collected from the annual reports of the sampled companies for the year-end on and after 31 December 2016. The data then was analyzed through content analysis method and independent t-test to accomplish the objective. This study found that the average proportion of women directors out of the total number of board members is 17% and the average age of the board members is 61 years old, which is above the minimum retirement age. In addition, it was also found that having women board members has a significant impact on a company’s SR but none on the aspects of age and ethnic diversity. Women directors have a different way of perception, thinking, and ideas that could influence companies’ sustainability initiative and reporting. The study contributes to the literature on corporate governance–sustainability by focusing specifically on the impact of board diversity on SR.